Performance Of Aceh's Gastronomic Entrepreneurs In The Digital Transformation Era: The Crucial Role Of Entrepreneurial Spirit And Dynamic Capabilities - Dhian Rosalina; Meutia Dewi; Iskandar Muda; Andri Soemitra; Yusrizal Yusrizal (UNIVED Press, 2025)
This study aims to analyze the influence of the entrepreneurial spirit on the dynamic capabilities and performance of Aceh traditional culinary Small Enterprises during the digital transformation era. Gastronomic entrepreneurs are culinary business actors who not only offer food products but also provide local cultural experiences to tourists. In an increasingly digital and competitive landscape, SMEs need to develop adaptive capabilities by reinforcing their entrepreneurial spirit. We PLS-SEM method, which involves 230 respondents from Culinary SMES. The findings indicate that the entrepreneurial spirit has a positive and significant impact on dynamic capabilities, directly enhancing the performance of culinary small enterprises (SMEs). Furthermore, dynamic capabilities also have a positive and significant impact on business performance. Mediation analysis reveals that dynamic capabilities act as a critical intermediary, strengthening the relationship between entrepreneurial spirit and SME performance. These findings confirm that adaptation to technology, risk-taking, and innovation are crucial factors in enhancing business performance.